Gerald Sutton Brown and the Discourse of City Planning Expertise in Vancouver, 1953–1959 - Langford, Will (Urban History Review / Revue d'histoire urbaine, 2013)
This paper examines the discourse Gerald Sutton Brown, the director of the newly created Vancouver Department of Planning, employed between 1953 and 1959. Amidst rapid urbanization and suburbanization, changes in local state governance, and wider debate over the urban future, Sutton Brown began speaking in public to popularize his vision of planning. He regularly compared planning to business, medicine, science, and politics. I argue that his co-optation of language, images, and metaphors drawn from more established professions promoted planning projects and asserted the authority of the planning profession. However, Sutton Brown’s rhetorical strategy obscured and depoliticized many of the realities of his high modernist planning program. Even if his discourse proved relatively ineffectual in the face of financial, political, and practical constraints, his rhetoric was important because it demonstrated one way that high modernist ideas could be mobilized to promote significant urban change.